2016
DOI: 10.1007/s00192-016-3128-z
|View full text |Cite
|
Sign up to set email alerts
|

Transobturator versus single incision slings: 1-year results of a randomized controlled trial

Abstract: The SI sling provides comparable objective efficacy to the TO sling at 1 year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Data searches were performed in Google Scholar, PubMed, Medline, Embase, Scopus, Web of Science and the Cochrane Database of Systematic Reviews. Finally, 29 studies , including a total of 2 986 women, were selected for the meta‐analysis. An SIMS was defined as a midurethral sling placed through a single vaginal incision without skin incision, and included the Mini‐Arc, Contasure‐Needleless, Ophira, tissue fixation system (TFS) and Ajust.…”
Section: Methodsmentioning
confidence: 99%
“…Data searches were performed in Google Scholar, PubMed, Medline, Embase, Scopus, Web of Science and the Cochrane Database of Systematic Reviews. Finally, 29 studies , including a total of 2 986 women, were selected for the meta‐analysis. An SIMS was defined as a midurethral sling placed through a single vaginal incision without skin incision, and included the Mini‐Arc, Contasure‐Needleless, Ophira, tissue fixation system (TFS) and Ajust.…”
Section: Methodsmentioning
confidence: 99%
“…The 55 articles were summarized chronologically in Table 1 with detailed information on study design, intervention and comparator, measurements of reported complications and follow-up duration that were listed by the following order: RCT, systematic review/meta-analysis and review [11–65] …”
Section: Resultsmentioning
confidence: 99%
“…[69] Women who develop post-surgical OAB and feel worse than their pre surgical status should be carefully evaluated. Palos et al, [11] [12] [13] 2018 RCT SI-MUS 84 TVT-O 41 18 mo Palpable mesh fiber on anterior vaginal wall in SI group (2.4%), else not mentioned Pascom et al, [14] [15] 2018 RCT TOT 75 36 mo Reintervention 5.2% Unintentional perforation 5.2% Post voiding residual 1% Dyspareunia 0% Tieu et al, [16] 2017 RCT TOT 42 12 mo De novo urgency 0.7% Repeat SUI surgery 12% Vaginal mesh exposure 6.1% Fernandez et al, [17] [20] 2016 RCT TVT 93 TOT 83 60 mo Vaginal mesh exposure TVT 2%, TOT 7% Urine retention requiring intervention TVT 6%, TOT 4% Substantial pain TVT 21%, TOT 10% Schellart et al, [21] TVT-O 0%, SI 0% Jurakova et al, [23] Vaginal tape erosion TVT-O 0%, SI 0% Gaber et al, [24] Martinez et al, [25] [26] 2015 RCT TOT 103 12 mo Repeat surgery 1.8% Groin pain 6.2% Tommaselli et al, [27] Laurikainen et al, [28] Nyyssönen et al, [29] 2014 RCT TVT 50 TOT 50 46 mo De novo urgency TVT 3%-25%%, TOT 6%-25% Scheiner et al, [30] [32] [33] 2014 RCT TVT 30 12 mo Bladder perforation 2.9% Djehdian et al, [34] [35] 2014 RCT TOT 87 12 mo UTI 4.2% Reoperation 3.1% Bladder retention 1% Wadie et al, [36] Basu et al, [37] 2013 RCT TVT 33 36 mo Repeat continence procedure 0% SUI symptoms 9% Mostafa et al, [38] [39] No postoperative urinary retention Schierlitz et al, [40]…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies were small, heterogeneous and at high risk of bias. [153][154][155][156][157][158][159] l Schellart et al 137 randomised 97 participants to the SIMS MiniArc and 96 participants to the SMUS Monarc (TO-TVT). At 1 year, the patient-reported (PGI-I scale) success rates were 83% and 86% (p = 0.46) for the MiniArc and Monarc groups, respectively, and the objective (CST) success rates were 89% and 91% (p = 0.65) for the MiniArc and Monarc groups, respectively.…”
Section: The Patient Global Impression Of Improvement Scalementioning
confidence: 99%
“…185 In the literature, 20 RCTs (n = 2613 participants) compared SIMSs with SMUSs with regard to LUT injuries. 86,90,138,141,154,155,157,158,160,162,164,[189][190][191][192][193][194][195][196][197] Pooled data favoured neither SIMSs nor SMUSs (RR 0.69, 95% CI 0.35 to 1.36).…”
Section: Intraoperative Injuriesmentioning
confidence: 99%